1952
DOI: 10.1039/tf9524800025
|View full text |Cite
|
Sign up to set email alerts
|

The pyrolysis of 1 : 2-dichloroethane

Abstract: The thermal decomposition of 1 : 2-dichloroethane has been re-examined and the results are compared with those of previous investigations. A fall in velocity constant of the chain part of the reaction has been observed on reducing the initial pressure below 20 mm. This is caused by a failure of one of the unimolecular steps of the chain reaction and the high pressure rate can be maintained below the critical limit by the addition of sufficient hydrogen chloride. The decomposition exhibits reproducible inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1962
1962
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The thermodynamic properties of species as inputs of the computer code are part of the reacting system in a standard format [Kee et al, 1990J, and such data are available [Kee et al, 1990]. Those species not available in We have developed a detailed chemical kinetic mechanism which is given primarily from Miller (1995) and are added partilly from a wide range of sources [Howlett, 1952;Bozzelli, 1995;Barton and Howlett, 1949;Leylegian et al, 1998]. This mechanism, which is reported elsewhere [Lee, 2oo0J, includes 260 elementary forward and backward reactions, and involves 44 gas-phase species.…”
Section: Numerical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermodynamic properties of species as inputs of the computer code are part of the reacting system in a standard format [Kee et al, 1990J, and such data are available [Kee et al, 1990]. Those species not available in We have developed a detailed chemical kinetic mechanism which is given primarily from Miller (1995) and are added partilly from a wide range of sources [Howlett, 1952;Bozzelli, 1995;Barton and Howlett, 1949;Leylegian et al, 1998]. This mechanism, which is reported elsewhere [Lee, 2oo0J, includes 260 elementary forward and backward reactions, and involves 44 gas-phase species.…”
Section: Numerical Approachmentioning
confidence: 99%
“…Many studies on the decomposition of EDC have been worked under the thermal decomposition [Barton, 1949;Barton and Howlett, 1949;Howlett, 1952;Holbrook et al, 1971, Ranzi et al, 1992Incavo, 1996], the catalysed pyrolysis by chlorine or other species [Ashmore et ai., 1982a;Ashmore et al, 1982b], and the photolysis [Yano and Tschulkow-Roux, 1980;Ma et al, 1990;Cardy et al, 1993]. The thermal decomposition is one of the most widely used methods in commercial processes for the production of vinyl chloride.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported the kinetic parameters for reaction R2 as k 2 = 7.6 × 10 10 exp(-411.7 kJ mol -1 /RT) s -1 at the G3MP2 level of theory. Howlett [5] reported the Arrhenius parameters for reaction R3 as k 3 = 1 × 10 13 exp(-292.9 kJ mol -1 /RT) s -1 . Salouhi et al [6] studied the pyrolysis of EDC over the temperature range of 763-793 K. They reported that overall rate constant of disappearance of EDC is independent to the temperature and its value is reported equal to 1.3 × 10 13 s -1 .…”
Section: Introductionmentioning
confidence: 99%
“…In some experiments propene (1.33 kPa) was added to the reaction mixture. Constant laser power levels of 2.5 to 9.5 W were used in the different runs. The extent of reaction was monitored by measuring both the major product and the remaining reactant by GLC.…”
mentioning
confidence: 99%